2024
DOI: 10.3390/ijerph21010060
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Online Peer Support for People with Young Onset Dementia

Esther Vera Gerritzen,
Martin Orrell,
Orii McDermott

Abstract: People with Young Onset Dementia (YOD) can be hesitant to engage with online peer support. This work aims to explore (1) why people are hesitant to engage in online peer support, (2) how to get more people involved in online peer support, and (3) what makes online peer support work well. Nine interviews with people with YOD were conducted on MS Teams. Participants were recruited through purposive sampling. Data were analysed thematically. Reasons for being hesitant to engage with online peer support include be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The barriers to accessing online peer support tended to be personal or systemic, with expectations of what is expected of them in the group, and making sure that the group would give them what they need, both reasons that people didn't engage. As with many of the studies highlighted in this systematic review, Gerritzen et al 90 also noted the advantages of online groups compared to in-personspecifically not having to travel and the greater potential to develop ad hoc relationships outside of support group meetings. Rapley et al 91 also demonstrated positive responses when exploring the use of videoconferencing for peer support among family carers of people with rarer dementia.…”
Section: Notable Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…The barriers to accessing online peer support tended to be personal or systemic, with expectations of what is expected of them in the group, and making sure that the group would give them what they need, both reasons that people didn't engage. As with many of the studies highlighted in this systematic review, Gerritzen et al 90 also noted the advantages of online groups compared to in-personspecifically not having to travel and the greater potential to develop ad hoc relationships outside of support group meetings. Rapley et al 91 also demonstrated positive responses when exploring the use of videoconferencing for peer support among family carers of people with rarer dementia.…”
Section: Notable Studiesmentioning
confidence: 76%
“…Although these more recently published papers would not have altered the overall themes or findings, it is necessary to provide some detail of these notable studies in the topic area. Gerritzen et al 90 conducted qualitative interviews with people with YOD, to understand why people may be hesitant to use online peer support groups, and how to overcome these hesitancies and improve engagement.…”
Section: Notable Studiesmentioning
confidence: 99%
“…In-person support groups have been shown to be beneficial in fostering the formation of friendships and a support network and allow for physical connection and support, which was noted to be missing by some participants using online-based services [13,30]. In-person support groups are also beneficial, as participants may not feel like they are speaking to a real person if participating in an online group format [31,32]. Furthermore, there may be technological challenges or barriers, such as accessing the internet and navigating technology, particularly for those who are visually impaired, often making in-person support groups preferable [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…In-person support groups are also beneficial, as participants may not feel like they are speaking to a real person if participating in an online group format [31,32]. Furthermore, there may be technological challenges or barriers, such as accessing the internet and navigating technology, particularly for those who are visually impaired, often making in-person support groups preferable [31,33]. Alternatively, online support groups can also be helpful, as they may be more accessible for people with dementia and their caregivers, who may feel more comfortable and less vulnerable in their home setting [30].…”
Section: Discussionmentioning
confidence: 99%